Clinical and Pathological Features of Lipid Storage Myopathy; A Retrospective Study of a Large Group from Iran - Nilipour, Yalda; Karimzadeh, Parveneh; Nafissi, Shahriar; Taghdiri, Mohammad Mahdi; Saneifard, Hedyeh; Shakiba, Marjan; Rahbarfar, Yalda (International Clinical Neuroscience Journal, 2020)
Background: Lipid storage myopathies (LSMs) are rare diseases. The phenotype and genotype of lipid metabolism disorders are heterogeneous and divided into two major groups. Constant or progressive proximal and axial muscle weakness associated with or without metabolic crisis, is often seen in patients with LSM such as primary carnitin deficiency (PCD) or multiple acyl-coenzyme a dehydrogenase deficiency disorder (MADD). On the other hand, rhabdomyolysis triggered by fasting, fever, or physical activity usually occurs in patients with disorders affecting intramitochondrial fatty acid transport and β-oxidation, such as carnitine palmitoyltransferase II deficiency (CPT2), mitochondrial trifunctional protein deficiency and very-long-chain acyl-CoA dehydrogenase deficiency (VLCAD). Methods: In this cross-sectional study, we summarized the clinical profiles and muscle histology of 64 Iranian patients diagnosed with LSM by muscle biopsy. These patients were selected from 3000 patients referred for muscle biopsy to Toos and Mofid children’s hospitals during 2010 to 2016. Their affected siblings were also added to the study. Result: In our study 45.3% of the patients were men and 54.7% were women. Mean age of the patients was 27.05 years (SD: 14.26) and the mean age of onset of symptoms in these patients was 20.94 (SD: 14.25) years. Most patients (70.3%) had proximal weakness and no bulbar involvement. Only 9.3% of the patients had a positive family history. Conclusion: LSMs are not incommon in Iran and their phenotype can mimic inflammatory myopathy or limb girdle muscular dystrophy. Overall the demographic and clinical features of LSMs in Iranian patients were similar to prior reports.